التسيير العمومي الجديد وأثره في تحسين أداء المؤسسة العمومية فيالجزائر دراسة حالة مديرية المصالح الفالحية لواليةالمسيلة - -حيقون أحمد -بنلمدللبلقاسم (My University, 2024)
Abstract This study sought to identify the new public management and its impact on improving the performance of the employees of the Directorate of Agricultural Services in the state of M’sila by identifying the relationship between the dimensions of the new public management represented by (the dynamic, participatory, strategic, ethical, decentralization and qualitative dimension…), so that a combination of the descriptive approach was relied upon. The analysis is appropriate to the subject of the study, and to achieve the objectives of the study, a questionnaire was designed that is compatible with the study and its objectives, for the purpose of collecting data from the sample members, which consists of (35) items and distributed to a sample of (40) individuals in the Directorate of Agricultural Services. (35) questionnaires were retrieved and to process the existing data. Within this, we relied on the statistical program (SPSS) to analyze the data, and in the end we achieved that all hypotheses were met
Keywords: لكلمات المفتاحية: التسيير العمومي الجديد، األداء، الموظفين